Rancang Bangun Sistem Informasi Nilai Akademik Pada SMP Negeri 6 Pelepat Ilir - Muhammad Muhammad; Sinta Maria; Mukhtar Mukhtar (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2023)
Value is the achievement of student learning outcomes cumulatively in a one semester. Cumulative means the average of the average value assignments, daily test, mid semester test and end of semester test. Then in every educational institution there is a KKM value (Minimum Completeness Criteria) which is a reference for completeness from the final result of student score. At this time, almost all educational institutions, both public and private, are careful in processing student score data, because of the importance of the value that will be issued to determine student achivment. The value data processing that occurs at SMP Negeri 6 Pelepat Ilir is currently still by copying or duplicating student data file, causing a buildup of data which has an impact on the difficulty of getting value data information because they have to open the data files one by one. The purpose of this study is to facilitate teachers in processing student score data at SMP Negeri 6 Pelepat Ilir by using the PHP programming language and using the phpmyadmin database. Thhe result of this study are the axistence of an information system for processing student grades data will provide convenience for teachers in processing student grades.